Quality of HIV care in the United Kingdom: key indicators for the first 12 months from HIV diagnosis. (28th August 2013) - Delpech, V; Brown, AE; Croxford, S; Chau, C; Polavarapu, V; Cooper, N; Rooney, G; Yin, Z
Abstract : Objectives: Prompt HIV diagnosis and treatment are associated with increased longevity and reduced transmission. The aim of the study was to examine late diagnoses and to assess the quality of care following diagnosis. Methods: National surveillance and cohort data were used to examine late HIV diagnoses and to assess the quality of care received in the 12 months following HIV diagnosis. Results: In 2011, 79% (4910/6219) of persons (15 years and over) diagnosed with HIV infection had CD4 counts reported within 3 months; of these, 49% were diagnosed late (CD4 count < 350 cells/μL). Adults aged 50 years and over were more likely to be diagnosed late (67%) compared with those aged 15–24 years (31%). Sixty‐four per cent of heterosexual men were diagnosed late compared with 46% of women and 36% of men who have sex with men (MSM) ( P < 0.01). The percentage of late diagnoses was highest among black African adults (66%) compared with other ethnicities; 96% of black African adults diagnosed late were born abroad. Overall, 88% and 97% of patients were linked to care within 1 and 3 months of diagnosis, respectively, with little variation by demographics and exposure category. The crude 1‐year mortality rate was 31.6 per 1000 persons diagnosed in 2010. It was highest among adults diagnosed late (40.3/1000 versus 5.2/1000 for prompt diagnoses) and particularly among those aged 50 years and over. Excluding deaths, 85% of the 5833 diagnosed in 2010 were retained in care in 2011; 92% of the 2264 adults diagnosed late in 2010 received antiretroviral therapy by the end of 2011. Conclusions: The National Health Service provides high‐quality care to persons newly diagnosed with HIV infection in the UK, with no evidence of health inequalities. Despite excellent care, half of adults are diagnosed late according to the threshold at which national guidelines recommend treatment should begin. Such patients have an 8‐fold increased risk of 1‐year mortality compared with those diagnosed promptly. Reducing late diagnosis of HIV infection remains a public health priority in the UK.